Control of Water Adsorption via Electrically Doped Graphene: Effect of Fermi Level on Uptake and H2O Orientation. Issue 18 (15th July 2021) - Bagheri, Morteza H.; Loibl, Rebecca T.; Schiffres, Scott N.
Abstract: The interaction of graphene with water molecules under an applied electric field is not thoroughly understood, yet this interaction is important to many thermal, fluidic, and electrical applications of graphene. In this work, the effect of electrical doping of graphene on water adsorption is studied through adsorption isotherms and current–voltage ( IV ) characterizations as a function of the Fermi level. The water adsorption onto graphene increases by ≈15% and the doping levels increase by a factor of three with a gate‐to‐graphene voltage of +20 or −20 V compared to 0 V for sub‐monolayer adsorption. This change in uptake is attributed to the increase in density of state of graphene upon electrical‐doping, which changes the Coulombic and van der Waals interactions. The water adsorption onto graphene is either n‐ or p‐doping depending on the applied gate‐to‐graphene voltage. The ambi‐doping nature of water onto graphene is due to the polar nature of water molecules, so the doping depends on the orientation of the water molecules. Abstract : The adsorption of water vapor onto undoped versus electrically doped graphene is examined through adsorption isotherms and current–voltage (IV) measurements. Electron‐ and hole‐doping both enhance water adsorption onto the surface due to the increased charge carriers in the graphene upon electrical‐doping. The orientation of the adsorbed water molecules, however, depends on the type of charge carriers in the graphene.